Stoma support garments: a survey on patient information needs, product selection and equity of provision. (2nd April 2020) - Taylor, Claire; Munro, Julie; Goodman, William; Beeken, Rebecca; Dames, Nicola; Oliphant, Raymond; Watson, Angus; Hubbard, Gill
Abstract : Many people with a stoma wear support garments, often a belt or underwear, to support the abdominal muscles, secure the stoma and conceal the appliance. There is some evidence that they reduce the risk of a parastomal hernia developing or getting worse. To investigate the experiences of UK adults living with a stoma regarding the use of support garments, a cross-sectional online survey was designed and distributed on social media and via a mailing list. The questionnaire was completed by 1528 people, 598 of whom answered a free-text question. These responses underwent thematic analysis. This article discusses the responses related to information provision, product selection and equity of provision, while separate articles discuss those related to the rationale for wearing stoma support garments. A third of respondents had not received any expert information on support garments and had to rely on their own research to make their selection. Of the 1004 who had received information, the main sources were stoma care nurses (73.4%), commercial suppliers (49.7%), peers (20.9%) and support groups (19.2%). Free-text comments indicated that respondents did not always feel they had been adequately counselled about support garments or shown the range available. Many respondents described restrictions being imposed on the number or range of products they could order. This study highlights the important role stoma care nursing specialists can play in assessment and review of support garments to ensure ostomates select the right product for their prescription.